Product-based and knowledge-based sustainable living practices: The case of IKEA - Canberk Yurt; Deniz Deniz (Sustinere: Journal of Environment and Sustainability, 2021)
Sustainable living is a key concept for eco-friendly lifestyles in consumer societies. Two major sustainable living solutions are based on knowledge and product. Their roles and impacts on sustainable living are controversial. Despite offering innovative approaches to sustainability solutions, products are consumption-dependent. On the contrary, knowledge-based solutions are resource-intensive, while technically resources are limited. This research analyzed the advantages and disadvantages of knowledge-based and product-based sustainable living solutions through a survey regarding environmental sensitivity and sustainable lifestyles from a specific local market. This study highlighted IKEA as the case. From the consumer’s point of view, some IKEA sustainable living dimensions are more knowledge-based, yet the rest of them are product-based. For holistic sustainable living solutions, the combination of the two is crucial. The findings of this study suggest strategies to increase individual and corporate awareness of sustainable living practices from knowledge and product perspectives. In this respect, this study is valuable for IKEA and other companies to revise their strategies in promoting sustainable living and guide sustainable consumer behavior.